Assessing landscape’s appropriateness of Muslim cemetery, Jalan Ampang - Albakeri, Norsyaza Husna; Othman, Jamilah (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2017)
The paper assesses on the landscape‟s appropriateness of Muslim cemetery, Jalan Ampang in relation to Shariah compliance. Cemeteries are the spaces where the deceased are buried in order to protect the bodies from scavengers, weather or hygienic conditions and sanitation. Cemetery is very important in Islam as it is one of the ways to remind people of death and hereafter. Thisstudy was conducted at the Muslim cemetery located in Jalan Ampang. The site was chosen due to its historic background asides from being among the highest populated cemeteries in Klang valley. Being the oldest cemetery in Kuala Lumpur, the preliminary survey at the site has discovered that it was unsystematically planned with no proper guidelines. The aim of the research is to recommend a minimal landscape guideline for Muslim cemetery. In order to achieve the aim, three objectives were formulated. Firstly, to document the design layout of Jalan Ampang Muslim cemetery. Secondly, to study the necessary design suitable for the visitors of Muslim cemetery. Lastly, to access the infrastructure required for Muslim cemetery based on Shariah compliance. The study used mix-method of qualitative and quantitative methods to gather relevant data for the research such as:preliminary study, direct observation and survey questionnaires. The finding showed that the layout of a Muslim cemetery of Jalan Ampang is not systematic as the arrangement of the cemetery is too packed and it creates inconveniece to the visitors to conduct their activities. Besides, the facilities provided are not well maintained in the aspects of maintenance, management and safety. Hence, this study is very significant because it can help to develop a better Muslim cemetery design that ensures the comfort of the users as well as fulfilling the Shariah laws.